Analysis of potential donors pool in Moscow region and cases of a removal internal organs for transplantation subjected to medical research in 2017 - V. A. Klevno; M. L. Arefev (Вестник трансплантологии и искусственных органов)
Aim: to analyze the pool of potential donors in the Moscow region from among the corpses received for forensic medical examination, the effectiveness of their use, the assessment of the participation of the forensic service in transplantation coordination.Materials and methods. The potential donors from among the dead persons in 2017 from various injuries were analyzed, the conclusions of forensic experts in cases of the removal of internal organs from the corpse were studied.Results. In 2017, 417 forensic examinations of corpses with open and closed isolated traumatic brain injuries received as a result of various injuries were conducted. 328 corpses of males and 89 females, dominated by the age group of 61 and above – 170 (40.7%). The period of hospitalization 2–7 days – 173 (41.8%). In addition, 76 cases of no traumatic hemorrhages in the brain and under the matter of the brain caused by diseases were studied, the age was more than 60 years – 41 (53.9%) prevailed. In 29 cases, internal organs were taken for transplantation. Such corpses were investigated in 15 forensic departments out of 47 (31.9%), which are part of 8 departments of the Ministry of health of the Moscow region out of 15. Among donors, the prevalence of men 27 (93%) over women 2 (7%) in the 31–60 age group is 19 (65.5%). 17 were diagnosed with brain death (58.6%) and 12 asystolic donors (41.4%). Multiorgan removal was carried out in 13 cases (44.8%), in 15 cases kidneys were removal (51.7%), 1 case of refusal of the removal after visual inspection of the extracted organ.Conclusion. The Analysis allows to estimation a possible pool of potential donors in the Moscow region, to correlate with the volume of removal organs, which indicates insufficient efficiency of their use. Insufficiently active participation of medical institutions of Administrations of transplantological coordination in the territory of the Moscow region correlates with participation of medico legal experts in this coordination. In the conclusions of the experts found no evidence of traumatic damage to the organ and the obstruction of the expert when giving answers to the questions of the investigatory organizations.